Ecotoxicity of selected antibiotics for organisms of aquatic and terrestrial ecosystems - Havelkova, Barbora; Beklova, Miroslava; Kovacova, Veronika; Hlávková, Daniela; Pikula, Jiri (Neuro-endocrinology letters, 2016)
OBJECTIVES: The aim of this study was to assess the ecotoxicity of selected antibiotics (i.e. penicillin G, vancomycin and tetracycline) using ecotoxicological tests. Tests were conducted on organisms representing all trophic levels of the aquatic ecosystem, namely producers (green freshwater algae Pseudokirchneriella subcapitata), consumers (water fleas Daphnia magna) and decomposers (bacteria Vibrio fischeri). The effect of antibiotics on the representative of edaphon was measured by testing the inhibition of the reproduction of springtails Folsomia candida and earthworms Eisenia fetida. DESIGN: Methodologically, the procedure was carried out in accordance with the following standards: OECD 201 (Fresh water algal growth inhibition test), OECD 202 (Inhibition of the mobility of Daphnia magna), ISO 11348-2 (Inhibitory effect of antibiotics on the light emission of Vibrio fischeri), OECD 232 (Inhibition of reproduction of Collembola Folsomia candida) and OECD 222 (Inhibition of reproduction of Eisenia fetida). RESULTS: In aquatic organisms the highest level of toxicity was shown by tetracycline to algae (72hEC50 = 1.82 mg.l-1) and daphnia (48hEC50 = 8.16 mg.l-1). The least toxic for all test organisms was penicillin G. The results of the tests performed on the representative of edaphon, Folsomia candida, showed that its reproduction was most inhibited by penicillin G (28dEC50 = 328 mg.kg-1) and least by tetracycline (28dEC50 = 2560 mg.kg-1). Similar results were observed in Eisenia fetida (56dEC50 = 348 mg.kg-1 for penicillin G and 56dEC50 = 2735 mg.kg-1 for tetracycline. CONCLUSION: The ecotoxicity of antibiotics differed significantly depending on the test organism and testing conditions.
Keywords: Animals; ekosystém; Toxicity Tests; látky znečišťující půdu; Ecosystem; zvířata; antibakteriální látky; Anti-Bacterial Agents; chemické látky znečišťující vodu; testy toxicity; Soil Pollutants; Water Pollutants, Chemical